Analisis Kebijakan Pengembangan Usaha Keluarga Sasaran Program Jaminan Sosial Cilegon Mandiri (KSJSCM) - Yeni Widyastuti (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2020)
Mayor Regulation No. 7 of 2017 concerning Jaminan Sosial Cilegon Mandiri. (JSCM) is a program that aims to support the fulfillment of basic needs, education, and family health of poor and disadvantaged people in the form of social assistance. One of the goals of this program is for the family who receives the program able to develop businesses that are managed continuously to improve family welfare. This paper tries to provide recommendations to policy implementers regarding policy alternative to develop and manage bussiness of target group (families that receive JSCM) by formulation of policy analysis issues, formulation of objectives, alternative policies, criteria and assessment of alternative policies and recommendations.